Assessing Selenium, Manganese, and Iodine Status in Pediatric Patients Receiving Parenteral Nutrition. (14th March 2017) - Johnsen, Jacob Clarke; Reese, Susan Anne; Mackay, Mark; Anderson, Collin R.; Jackson, Daniel; Paul, Irasema Libertad
Abstract : Background: Pediatric patients who are receiving parenteral nutrition (PN) unsupplemented with trace minerals can become deficient. Due to shortages in trace mineral products and the 2004 American Society for Parenteral and Enteral Nutrition report stating that individualized trace element supplementation may be warranted, a review was conducted concerning the trace minerals selenium (Se), manganese (Mn), and iodine (I). Method: A retrospective review of pediatric patients receiving PN that contained Se and Mn was conducted to determine if a difference existed between them and patients receiving PN without Se and Mn. Statistical analysis was done to assess a difference between trace mineral levels and the time to deficiency between supplemented and unsupplemented patients. Unsupplemented I patients had urine I levels assessed to determine deficiencies in patients receiving PN. Results: Plasma Se levels were measured at a mean of 20 days for supplemented patients (n = 131) and 19 days for nonsupplemented patients (n = 57) with no difference between groups ( P = .2973). Plasma Mn levels were measured at a mean of 28 days, showing no statistical difference ( P = .721). Of the 177 nonsupplemented I patients, 74% demonstrated I deficiencies without supplementation. Conclusions: Time to the development of a Se, Mn, or I deficiency is important to guide supplementation of exclusive PN in children when trace mineral products are short in supply. Our retrospective experience supports assessment of the trace minerals Se at 21 days and Mn at 30 days. It also suggests that some pediatric patients receiving PN are deficient in I.